Analysis of Performance on Substrate Culture Made from Natural Materials for Green Roof Technology - กิติอนันต์ภัทร์, วรินทร; ศิวดำรงพงศ์, สมศักดิ์; ธีรอำพน, อารักษ์ (Progress in Applied Science and Technology, 2019)
Currently, Climate Change caused by greenhouse gas which generated with rate of city’s growth and decrease of green area. These led to heat absorbs area as a result is urban heat island. Therefore reducing global warming (Greenhouse effect) is the first priority to deal with the problem. One potential solution was to increase green area by planting the green roof. This study was proposed the analysis of performance on substrate culture made from natural materials for green roof due to lighter weight of natural material than soil which impact to roof structure and its cost. This research was focused on extensive green roof and 3 kinds of materials, coconut fiber-dust, coffee residue and paddy husk charcoals with using starch as binder. Manila grass was selected to plant into the 5 cm thick substrate culture in metal sheet tray size 50x50x10 cm. 2k factorial design technique was employed to analyze the substrate culture performance. The main nutrients of the substrate, N P K, were measured to describe the results. It was found that the most appropriate substrate was coconut fiber-dust : coffee residue : paddy husk charcoals 60:30:10 with starch 20 percent which yield the growth of grass in the same level as soil with lower weight than soil by 7 times.